An untargeted metabolomic analysis of acute AFB1 treatment in liver, breast, and lung cells - Heidi H. Cao; Sabrina Molina; Susan Sumner; Blake R. Rushing (PLoS ONE, 2025)
Aflatoxin B1 (AFB1) is a class 1 carcinogen and mycotoxin known to contribute to the development of hepatocellular carcinoma (HCC), growth impairment, altered immune system modulation, and malnutrition. AFB1 is synthesized by Aspergillus flavus and is known to widely contaminate foodstuffs, particularly maize, wheat, and groundnuts. The mechanism in which AFB1 causes genetic mutations has been well studied, however its metabolomic effects remained largely unknown. A better understanding of how AFB1 disrupts metabolism would provide insight into how this mycotoxin leads to carcinogenesis, growth impairment, and/or immunomodulation, and may reveal potential targets for pharmacological or nutritional interventions to protect against these effects. The current study evaluated the metabolomic effects of various doses (2.5 μM, 5 μM, 10uM) of AFB1 treatment to HepG2 (liver), MDA-MB-231 (breast), and A549 (lung) cells. Treated and control cells’ metabolomic profiles were evaluated via ultra-high performance liquid chromatography-high resolution mass spectrometry (UHPLC-HRMS). Univariate and multivariate analyses revealed significant alterations in metabolite concentrations from each dose of AFB1 treatment in each cell type. Pathway analysis was then used to understand broader biochemical functions affected by AFB1 treatment in each cell type. HepG2 cell pathway analyses revealed significant pathway perturbations in lipid metabolism, carnitine synthesis, catecholamine biosynthesis, purine metabolism, and spermidine and spermine biosynthesis. Analysis of A549 cells found a greater emphasis of perturbations on various amino acids along with lipid synthesis-related pathways, and catecholamine biosynthesis. Finally, analysis of treated MDA-MB-231 cells found spermidine and spermine biosynthesis, carnitine synthesis, plasma membrane-related pathways (phosphatidylcholine synthesis and alpha linolenic acid and linoleic acid metabolism), and various amino acid metabolism pathways to be most affected. These highlighted pathways should be targeted in future investigations to evaluate their potential in mitigating or preventing the development of negative health effects associated with AFB1 exposure.